2018
DOI: 10.1007/s10029-017-1717-5
|View full text |Cite
|
Sign up to set email alerts
|

Invited comment to: European Hernia Society guidelines on prevention and treatment of parastomal hernias

Abstract: Parastomal hernia is the most frequent problem encountered after an enterostomy procedure. Even with advances in colorectal surgery, the creation of a stoma will probably not disappear in the near future. There are varying incidences of parastomal hernia formation depending on the type of colostomy or enterostomy done with the end colostomy having the highest in terms of parastomal hernia formation. Even the type of repair for this type of hernia is plagued with challenges due to its high recurrence rate.We at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 0 publications
0
46
1
Order By: Relevance
“…This significant decrease in size leads to an insufficient parietal coverage and may induce PSH. Intraperitoneal location is not always simple and requires training, although the Sugarbaker technique is largely performed for PSH repair 5,6 . However, this technique, without mesh opening, should theoretically reduce the risk of shrinkage and PSH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This significant decrease in size leads to an insufficient parietal coverage and may induce PSH. Intraperitoneal location is not always simple and requires training, although the Sugarbaker technique is largely performed for PSH repair 5,6 . However, this technique, without mesh opening, should theoretically reduce the risk of shrinkage and PSH.…”
Section: Discussionmentioning
confidence: 99%
“…The morbidity of these procedures varies from 10% to 30%, and recurrence rates up to 75% have been reported if no mesh is used 2 . The most effective technique is certainly the Sugarbaker technique, 5 but it requires insertion of a mesh in an underlay position (intraperitoneally) that may induce bowel adhesion or erosion 6 …”
mentioning
confidence: 99%
“…Similarly, in parastomal hernias, the correct use of mesh is less established. The most recent guidelines for the treatment of parastomal hernias are the European hernia society guidelines on the prevention and treatment of parastomal hernias 9 . Here they recommend against a simple suture repair in elective parastomal hernia repair, but do not give any recommendations for emergency repair.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is still no consensus on the utility of permanent sigmoidostomy in the prevention of PSH. The European Hernia Association argues that there is insufficient evidence supporting that extraperitoneal colostomy has an advantage in reducing the incidence of PSH compared with transperitoneal colostomy 11 . However, some meta‐analyses have indicated that the technique of extraperitoneal colostomy significantly lowers the incidence of PSH 12,13 …”
Section: Introductionmentioning
confidence: 99%